Pengaruh Informasi Akuntansi Terhadap Harga Saham Perusahaan - Wirasmo, Syakhira Garthakusuma; Fauzan, Fauzan (ITB AAS INDONESIA, 2024)
Among the most favored investment sectors are stocks in the real estate and property industry. Furthermore, the real estate and property sector indicates a nation's economic growth or contraction. Property prices are predicted to be weak in early 2024 while Bank Indonesia's benchmark interest rate remains high at 6%. Due to consumers being cautious when taking out loans to buy property and because of high share prices, these high interest rates will have a detrimental effect on the real estate market. This study aims to analyze the influence of earning per share, return on assets, return on equity, and debt to equity on stock price. A linear regression analysis is used to accomplish the objective of the research using the data from the Indonesia Stock Exchange which lists property and real estate sector for the 2019-2023 period. This research uses a quantitative approach method with multiple linear regression analysis techniques using SPSS. The sampling technique used purposive sampling technique and obtained 24 companies with a total of 108 data. The results of this research show that EPS, ROA, ROE have a positive effect on stock prices, meanwhile DER is not affect to stock prices.